Implikatur Konversasional dan Konvensional sebagai Strategi Humor dalam Acara “Lapor Pak!”: Conversational and Conventional Implicatures as Humor Strategies in the Show “Lapor Pak!” - Apriani, Yeni; Setiawan, Teguh; Wibowo, Anindia Wahyu Pratiwi Randri (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
This study examines the types and forms of implicatures used as humor strategies in the Indonesian digital comedy talk show “Lapor Pak!”. This study is motivated by the prevalence of utterances containing implied meanings in multi-party interactions among the players, making them interesting for pragmatic analysis. This study aims to describe the types of conversational and conventional implicatures and their linguistic realizations such as declarative, interrogative, imperative, and exclamatory as humor strategies in multi-party conversations. A descriptive qualitative approach is used, with data sourced from the actors’ utterances in the episode Lagi, “Komandan Ussy Bikin Andhika Tak Berkutik!” uploaded on the YouTube channel 7 Comedy. Data were collected through observation and recording techniques and analyzed using pragmatic identity and distribution methods. The findings indicate two types of conversational implicatures (11 data) and conventional implicatures (4 data). Conversational implicatures arise from the neglect of the maxims of Quality and Relevance (Grice, 1975), which trigger hyperbole and cognitive dissonance, while conventional implicatures are triggered by specific lexical meanings (attraction, bete) that function as reframing and metapragmatic commentary. These two types are manifested in declarative, interrogative, imperative, and exclamatory sentences. The main findings indicate that humor in multi-participant situational comedy is not produced by a single utterance but is constructed collaboratively through sequential responses and negotiation of meaning among participants. This research enriches the study of pragmatics by revealing the relationship between types of implications and mechanisms of collaborative humor in multi-participant conversations, extending the application of Grice's pragmatics beyond monologue or formal discourse.